Selected Copper‐Based Reactions for C−N, C−O, C−S, and C−C Bond Formation. Issue 51 (15th November 2017) - Bhunia, Subhajit; Pawar, Govind Goroba; Kumar, S. Vijay; Jiang, Yongwen; Ma, Dawei
Abstract: Metal‐catalyzed cross‐coupling reactions belong to the most important transformations in organic synthesis. Copper catalysis has received great attention owing to the low toxicity and low cost of copper. However, traditional Ullmann‐type couplings suffer from limited substrate scopes and harsh reaction conditions. The introduction of several bidentate ligands, such as amino acids, diamines, 1, 3‐diketones, and oxalic diamides, over the past two decades has totally changed this situation as these ligands enable the copper‐catalyzed coupling of aryl halides and nucleophiles at both low reaction temperatures and catalyst loadings. The reaction scope has also been greatly expanded, rendering this copper‐based cross‐coupling attractive for both academia and industry. In this Review, we have summarized the latest progress in the development of useful reaction conditions for the coupling of (hetero)aryl halides with different nucleophiles. Additionally, recent advances in copper‐catalyzed coupling reactions with aryl boronates and the copper‐based trifluoromethylation of aromatic electrophiles will be discussed. Abstract : Recent advances in copper/ligand‐catalyzed cross‐couplings of (hetero)aryl halides and nucleophiles, copper‐catalyzed coupling reactions with aryl boronates, and copper‐enabled trifluoromethylations of aromatic electrophiles are discussed in this Review.